The Experiencess of the The Student Volunteers of the Colege of Nursing in Responding to the Helath Needs of Mothers - Gloria, Grace A. (Silliman Journal, 2022)
This article reports the work experience of students of the College of Nursing with the mothers in promoting primary health care. Participating in the service-learning program as volunteers and supervised by resource persons from the college, the students pursued a health education program with mothers regarding dengue fever prevention, reproductive health particularly on family planning, skills training on herbal medicine making, and management of common home emergencies. They also engaged in actual provision of health services. As reflected in their journals, the students did not only improve their skills but they also learned to value community work. Specifically, they learned the values of teamwork, application and learning new principles and strategies, enhancement of personal skilk- and attitudes, and developed the desire to further improve their professional knowledge and skills. The internal motivation to share and contribute in community development was a factor that facilitated learning.